ОСОБЛИВОСТІ СУЧАСНИХ ІНСТРУМЕНТІВ ІНТЕРНЕТ-МАРКЕТИНГУ - Vikarchuk, Olga; Yushkevych, Olena (Zhytomyr Ivan Franko State University, 2021)
The article considers modern tools of Internet marketing as a set of actions aimed at attracting attention to the product or service sold by the company, and promoting the site in order to successfully sell the product. Theoretical foundations of Internet marketing and application of Internet marketing tools are defined and analyzed. Recommendations on introduction of innovative trends of Internet marketing in the operation of modern enterprises are developed. Internet marketing tools have been reviewed and characterized, such as: SEO-optimization, i.e. search engine promotion; E-mail; advertising on social networks (SMM); contextual advertising, one of the most popular advertising methods on the Internet; banner advertising, graphic image is located on the website page Publisher; traffic arbitrage, purchase by a webmaster of traffic at a certain price for resale on better terms. The main trends that dominate the field of Internet marketing are identified and analyzed, namely: dynamic activation of mobile marketing, active use of web analytics, advertising in video format, influencer marketing (a strategy that requires special people to reach the desired audience), Email marketing, content marketing, Instagram promotion, chatbots and messengers, the transition from individualism to collaborative creativity. It has been determined that the use of Internet marketing tools helps to promote the brand, attract customers, conduct market research and perform many other processes. Conversely,  significantly more resources would be necessary in an offline environment. It is concluded that Internet technologies are changing the way companies interact with their employees, partners, competitors and suppliers, at the same time Internet marketing is evolving with incredible speed, and only those who are able to change and adapt to the new business conditions are catching up with new trends and think of a quality marketing strategy.